The interaction between banking sector and financial technology companies: Qualitative assessment - a case of Lithuania - Ruihui Pu; Deimante Teresiene; Ina Pieczulis; Jie Kong; Xiao-Guang Yue (Risks, 2021)
The role of financial technology companies increases every day. From one side this process generates more possibilities for consumers from other side it is related with new risks which arise in banking sector. At the beginning of FinTech era lots of analyst were discussing about disruptive potential in financial services. Later, however, we can see more discussions about cooperation between FinTech companies and banks. The other point which is very important to discuss about is a financial inclusion. The purpose of this study is to analyze the interaction between banking sector and FinTech companies. We use a case study of Lithuania because here FinTech sector is growing very intensively. First of all we try to analyze the scientific literature which analyzes the main aspects of FinTech sector. The second part of the article provides the progress of the FinTech sector and presents the main points of methodology. The research of the FinTech sector in Lithuania was focused on strengths, weaknesses, opportunities, and threats (SWOT) and political, economic, social, technological, environmental, legal (PESTEL) analysis and main statistical parameters. We also used a correlation and regression analysis together with qualitative assessments. Our results showed that in order to value the interaction between banking and financial technology better to focus on qualitative assessment because only statistical analysis can give different and wrong results. We identified that both sectors interact with each other and there is no a disruptive effect of FinTech in Lithuania.
Keywords: G1; G2; 330; banking sector; financial inclusion; financial technologies; PESTEL analysis; risk; SWOT analysis